The subject advantage in relative clauses: A review. Issue 1 (5th April 2021) - Lau, Elaine; Tanaka, Nozomi
Abstract : The question of whether there exists a universal subject preference in relativization has stimulated research in a wide range of languages and across different domains, yielding an extensive body of literature in relative clause acquisition and processing. In this article, we aim at consolidating the efforts of existing research in order to inform further exploration of the universality of the subject preference with a comprehensive analysis of relevant work (including journal articles on empirical studies, dissertations, and conference proceedings). We present an overview of the proposals regarding the source(s) of the subject-object asymmetry from a cross-linguistic perspective and discuss commonly used methodologies in this research area, and we survey the research on relative clause processing and acquisition of different linguistic communities, including native speakers, second language learners, clinical populations, and heritage speakers.